PREVALENCE AND CHARACTERISTIC MULTIDRUG RESISTANT ORGANISMS IN INTENSIVE CARE UNIT OF Dr. WAHIDIN SUDIROHUSODO HOSPITAL MAKASSAR - Sitti Khadijah; Irda Handayani; Nurhayana Sennang (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
INTRODUCTIONAntibiotic is antibacterial substance produced by microorganisms which is supress other organisms growth. First antibiotic (penicillin) was found in 1928 by Alexander Fleming,who is a microbiologist from England. In 1930, penicillin begins given to infected patient. However, there is a resistant to penicillin called penicillinase.Antibiotic resistant is an increase of bacteria ability to antibiotic which is given. This cause bacteria does not responsive to antibiotic. When this organisms spread in community will threaten people and emerge new infection,which is more difficult to cure and increase cost of treatment. It will prolong patient’s length of stay, and increase mortality rates.Multidrug resistant organisms is microorganisms, most of it is bacteria, resistant to one or more class of antibiotic. In spite of, term of certain MDRO describe to resistant of one agent. For example, methicillin resistant Staphylococcus aureus (MRSA), vancomycin resistant Enterococcus (VRE), Vancomycin resistant Staphylococcus aureus (VRSA) dan Multidrug resistant Acinetobacter baumannii (MDRAB). These patogens are resistant to antimicrobe agent often used. This high resistant organisms necesssary to be more noticed in healthcare facilities. Except MRSA and VRE, there is other kind of MDRO such as Enterobacteriaceae produces- Extended spectrum beta-lactamase (ESBL) dan Klabsiella penumoniae carbapenemase producer (KPC). Multidrug resistant organisms implicates significant to infection management which is not found yet whether only limited handle based on prior isolation manual.Statistical data showed that prevalence of MDRO in Indonesia increases every year. Prevalence of MRSA in 1986 is 2,5% dan increased to 23,5% in 2006. Prevalence of Enterobacteriaceaeproduces ESBL in Harapan Kita hospital gain 16% which main caused in pediatric intensive care unit (PICU) is Klebsiella pneumoniae (14%) and second most agent caused is E. Coli (19%) (Winarto,2009). There was a research study in 2010 about Staphylococcus aureus sensitivity to vancomycin in Margono Soekarjo Purwokerto Hospital, Jawa Tengah, and it was found VRSA in 10 from 60 samples (15,6%) by stetoscope membrane. In United States by year 2000, it was 25,9% Enterococcus isolated by blood samples proved that resistant to vancomycin.Hospitalcare facilities are very vary by physical and functional characteristics of intensive care unit, burn injury unit, neonatal intensive care unit (NICU). A patient maybe infected to MDRO. A patient who had been infected may contaminate the infection to others sick or healthy people. Medical officer maybe one of elemen risk spreading infection when they ignore the rules of infection precaution and five moments handwash. Five moments consist of before contact to patient, before doing a patient, after doing a patient, after contact to patient, and after contact to patient’s neighbourhood.